Investigating Students' Conceptual Knowledge of Quantum Physics to Improve the Teaching and Learning Process - Patricija Nikolaus; Mile Dželalija; Ivana Weber (MDPI AG, 2024)
Research in the field of quantum physics is important for progress in many areas of exploration and development. Quantum computers and other quantum devices are promising technologies with numerous potential applications. On the other hand, understanding, interpreting, teaching, and learning quantum physics as part of an educational process is a major challenge. In the Republic of Croatia, students usually come in contact with the concepts of quantum physics towards the end of their high school education. These concepts are often abstract and represent a remarkable leap from the theories of classical physics. The aim of this study is to test the measurement properties of the instrument used to assess the progress of understanding and knowledge of quantum physics in a sample of Croatian high school students. The quantum physics conceptual survey (QPCS), developed and first tested in 2006 by Wuttiprom et al. at the University of Sydney, was the instrument we used in this study. The test was administered to 76 high school students. The results show that the QPCS test is valid and generally reliable in the context of Croatian secondary education, but for the topics Waves and particles and Uncertainty principle, the reliability needs further investigation. The results of the pretest and posttest were analysed and compared with each other and with previously published results. Quantitative methods were used to analyse the results obtained. We present several possible solutions to improve the teaching process, that we expect will lead to better results, especially for topics that are challenging for students.